Impact Analysis of Inflation on Social & Psychological Aspects in Nepal (Patan Prospective Journal, 2024)
This paper assesses the impact of inflation caused by the earthquake and the pandemic that took place in 2015 and 2019 respectively. Both of the natural disasters affected the economic health of Nepal adversely. The article has uncovered the repercussion of both the hazards in the social and psychological lives of Nepalese people. The major objective of the research has been to explore the implications of inflation in social and psychological aspects of the people in general and children in particular. The behaviors of children primarily in the downtrodden families have been found rude and anti-social because of their exposure to the hardships and challenges faced by their parents in the aftermath of the earthquake and the pandemic. The paper has been drafted based on the secondary resources. The method as used is the mixed research design as the article consists of both qualitative and quantitative data. The main finding of the research is that the government failed to do two things in the aftermath to address the social and psychological implications of the events. The first the government should have reformulated the policies to mitigate the inflation and the secondary it should have allocated a separate budget for the underprivileged communities so that they could come to normalcy in the aftermath.